2020
DOI: 10.14710/jkt.v23i2.7048
|View full text |Cite
|
Sign up to set email alerts
|

Karakter Anatomi Daun sebagai Bentuk Adaptasi Tumbuhan Penyusun Zonasi Mangrove di Banggai Kepulauan, Provinsi Sulawesi Tengah

Abstract: Mangrove is an essential ecosystem that are located in the transition area of fresh and sea water. Therefore, species that grow are typical species that are able to adapt to the saline environment. The aim of this research is to characterize leaf anatomical structure for every species that compose the communities found in each mangrove zonations, including their similarities and dissimilarities characteristic. Sampling of examined leaf was carried out in the mangrove areas of Peling Island and Bakalan Island b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 17 publications
0
12
1
2
Order By: Relevance
“…However, the number of mangrove species on the north coast of Bangkalan is still lower compared with the number of mangrove species found in the Mimika Region, Papua where 66 mangrove species consisting of 20 major, 10 minor, and 36 associate mangrove species were found (Setyadi et al 2021); and lower compared with Karimunjawa Island, Central Java with 24 species of mangrove (Rahmandhana et al 2022). The difference in the composition of mangroves at different stations is thought to be due to differences in environmental parameters, Tihurua et al (2020) stated that leaf anatomy is influenced by differences in environmental parameters, one of which is salinity affects the thickness of the watershed, and the density of the stomata. Different mangrove diversity may be caused by the difference in land elevation, which will cause different tides and salinity, which eventually can control mangrove diversity (Setyadi et al 2021).…”
Section: Mangrove Species Compositionmentioning
confidence: 93%
“…However, the number of mangrove species on the north coast of Bangkalan is still lower compared with the number of mangrove species found in the Mimika Region, Papua where 66 mangrove species consisting of 20 major, 10 minor, and 36 associate mangrove species were found (Setyadi et al 2021); and lower compared with Karimunjawa Island, Central Java with 24 species of mangrove (Rahmandhana et al 2022). The difference in the composition of mangroves at different stations is thought to be due to differences in environmental parameters, Tihurua et al (2020) stated that leaf anatomy is influenced by differences in environmental parameters, one of which is salinity affects the thickness of the watershed, and the density of the stomata. Different mangrove diversity may be caused by the difference in land elevation, which will cause different tides and salinity, which eventually can control mangrove diversity (Setyadi et al 2021).…”
Section: Mangrove Species Compositionmentioning
confidence: 93%
“…Mangrove ecosystems have a unique character compared to other types of ecosystems due to the formation of zoning [24]. Mangrove zoning is divided into four zones: open zone, middle zone, brackish zone, and terrestrial zone [9].…”
Section: Mangrove Zoning Patternmentioning
confidence: 99%
“…Therefore, there are different types of mangroves in each zone. It is by Tihurua et al [24] suggest that the zoning formed has a different species composition and structure because there is an adaptation for each species to its habitat. Furthermore, Arief [2] reported that the frequency of inundation, receiving sufficient freshwater supply from land through river flow, and being protected from large waves and strong tidal currents determine the composition of mangrove forest vegetation.…”
Section: Environmental Factors Affecting Mangrove Zoningmentioning
confidence: 99%
“…Hipodermis pada tanaman lada terletak di sebelah dalam jaringan epidermis. Hipodermis terletak pada kedua sisi jaringan epidermis (jaringan epidermis atas dan jaringan epidermis bawah) dan berfungsi sebagai tempat penyimpanan air (Tihurua et al, 2020). Pada penelitian ini, terlihat bahwa ukuran sel hipodermis atas maupun bawah pada daun lada sehat dan sakit tidak ada perbedaan yang nyata.…”
Section: Hasil Dan Pembahasanunclassified